2017
DOI: 10.1007/s10545-017-0023-9
|View full text |Cite
|
Sign up to set email alerts
|

Inborn errors of metabolism associated with psychosis: literature review and case–control study using exome data from 5090 adult individuals

Abstract: A literature review was conducted, using the computerized "Online Mendelian Inheritance in Man" (OMIM) and PubMed, to identify inborn errors of metabolism (IEM) in which psychosis may be a predominant feature or the initial presenting symptom. Different combinations of the following keywords were searched using OMIM: "psychosis", "schizophrenia", or "hallucinations" and "metabolic", "inborn error of metabolism", "inborn errors of metabolism", "biochemical genetics", or "metabolic genetics". The OMIM search gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Phenylketonuria (PKU-OMIM #261600) is a condition caused by a mutation in the PAH gene, which leads to a deficiency in phenylalanine hydroxylase, ultimately resulting in the build-up of Phe in the body. It can present with elevated levels of Val, Ile, and Leu, as well as allo-isoleucine, and different neuropsychiatric symptoms(Muelly et al, 2013;Trakadis, Fulginiti, & Walterfang, 2017).Moreover, mitochondrial diseases, such as myopathy, encephalopathy, lactic acidosis, and stroke (MELAS) syndrome (OMIM #540000), present with increased levels of Lac and Ala in blood and multisystemic symptomatology, including psychiatric features (Magner et al, 2014; Morava et al, 2010; Trakadis et al, 2017).Furthermore, a number of genetic conditions exist that are caused by deficiencies in glutamate metabolism and glutathione metabolism, respectively. Meanwhile, Tyrosinemia types I (OMIM #276700), II (OMIM #276600), and III (OMIM #276710) are all genetic conditions known to impact on the Tyr metabolism pathways, which can lead to neurodevelopmental or behavioral abnormalities(Bendadi et al, 2014;Ellaway et al, 2001;Fois et al, 1986;Mayorandan et al, 2014;Pohorecka et al, 2012).Another aminoacidopathy that needs to be mentioned is Maple syrup urine disease (MSUD -OMIM #248600).…”
mentioning
confidence: 99%
“…Phenylketonuria (PKU-OMIM #261600) is a condition caused by a mutation in the PAH gene, which leads to a deficiency in phenylalanine hydroxylase, ultimately resulting in the build-up of Phe in the body. It can present with elevated levels of Val, Ile, and Leu, as well as allo-isoleucine, and different neuropsychiatric symptoms(Muelly et al, 2013;Trakadis, Fulginiti, & Walterfang, 2017).Moreover, mitochondrial diseases, such as myopathy, encephalopathy, lactic acidosis, and stroke (MELAS) syndrome (OMIM #540000), present with increased levels of Lac and Ala in blood and multisystemic symptomatology, including psychiatric features (Magner et al, 2014; Morava et al, 2010; Trakadis et al, 2017).Furthermore, a number of genetic conditions exist that are caused by deficiencies in glutamate metabolism and glutathione metabolism, respectively. Meanwhile, Tyrosinemia types I (OMIM #276700), II (OMIM #276600), and III (OMIM #276710) are all genetic conditions known to impact on the Tyr metabolism pathways, which can lead to neurodevelopmental or behavioral abnormalities(Bendadi et al, 2014;Ellaway et al, 2001;Fois et al, 1986;Mayorandan et al, 2014;Pohorecka et al, 2012).Another aminoacidopathy that needs to be mentioned is Maple syrup urine disease (MSUD -OMIM #248600).…”
mentioning
confidence: 99%
“…Inborn errors of metabolism (IEM) are associated with various psychiatric manifestations. As reported by Trakadis et al, psychosis can be a predominant feature or even isolated presenting manifestation of IEM . We read with great interest the authors' overview of IEM that may be phenotypically difficult to distinguish from psychiatric illness.…”
Section: Summary Of Aceruloplasminemia Which Can Present With Psychosmentioning
confidence: 82%
“…As reported by Trakadis et al, psychosis can be a predominant feature or even isolated presenting manifestation of IEM. 1 We read with great interest the authors' overview of IEM that may be phenotypically difficult to distinguish from psychiatric illness. Within the group of metal storage disorders, pantothenate kinase-associated neurodegeneration and neuroferritinopathy represent two forms of neurodegeneration with brain iron accumulation (NBIA) that have been associated with psychosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Trakadis et al (2017) recently reported a significant mild enrichment (odds ratios between 1·13-1·64) in an unselected group of 2545 adults with SCZ from the Database of Genotypes and Phenotypes of rare, presumed functional variants in several IEM genes, including NPC1 and NPC2 (associated with Niemann-Pick disease type C (NPC)), ATP7B (associated with Wilson disease (WD), and CBS (associated with homocystinuria (HOM)). 7 It is unclear how well the patient cohort was characterized, as well as how many of the identified rare variants are known to be associated with disease or how strongly they are predicted to be pathogenic. The authors suggest the need for a prospective study to document the prevalence of such IEMs in patients with psychosis.…”
Section: Introductionmentioning
confidence: 99%